2010
DOI: 10.1111/j.1600-048x.2010.05002.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of extra‐pair paternity and conspecific brood parasitism in mallards Anas platyrhynchos using non‐invasive techniques

Abstract: A method that was based on non‐invasive sampling of genetic material was used to determine the rates of extra‐pair paternity (EPP) and conspecific brood parasitism (CBP) in mallards. Maternal and offspring DNA were extracted from feathers in nest material and hatched eggshell membranes. Using 8 microsatelite loci, extra‐pair offspring were detected in 48% of nests and accounted for 9.3% of all offspring. In addition, 10.1% of the offspring were confirmed to result from CBP, and 24% of all nests contained at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…However, mallard females engage in intraspecific brood parasitism, with almost one quarter of all nests experiencing egg dumping (Kreisinger et al . ). Thus, the high repeatability of eggshell coloration within females suggests that females could use inter‐individual differences in eggshell coloration to increase likelihood of detection of brood parasites.…”
Section: Discussionmentioning
confidence: 97%
“…However, mallard females engage in intraspecific brood parasitism, with almost one quarter of all nests experiencing egg dumping (Kreisinger et al . ). Thus, the high repeatability of eggshell coloration within females suggests that females could use inter‐individual differences in eggshell coloration to increase likelihood of detection of brood parasites.…”
Section: Discussionmentioning
confidence: 97%
“…Microsatellite methods require DNA, which has been sampled invasively by blood draws (Tiedemann et al, ) and noninvasively from nest bowls in the form of feathers, hatch membranes and eggshells (Kreisinger et al, ). We found success with both feathers and hatch membranes in this project, but we did not find eggshells to be reliable even though previous work has shown that eggshells contain nuclear DNA (Egloff, Labrosse, Hebert, & Crump, ).…”
Section: Discussionmentioning
confidence: 99%
“…From feathers, we used a portion of the calamus, targeting the superior umbilicus indicated by a red dot where blood commonly clots (Figure ; Horvath, Martinez‐Cruz, Negro, Kalmar, & Godoy, ). For hatch membranes, we used ~25 mg of hatch membrane targeting chorionic vessels containing embryonic DNA (Figure ; Kreisinger, Munclinger, Javukova, & Albrecht, ). For eggshells, we used ~70 mg of eggshell removed from hatch membrane carefully to avoid cross contamination from hatch membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellite genotyping of samples derived non-invasively from bird nests is effective in addressing these issues with minimal adverse effects on populations (e.g. Pearce et al 1997;Kreisinger et al 2010). This method allows estimations of renesting rates, breeding fidelity and research on alternative reproductive strategies such as conspecific brood parasitism (CBP) or extra pair paternity (EPP).…”
mentioning
confidence: 99%